Timing of last deglaciation in the Cantabrian Mountains (Iberian Peninsula; North Atlantic Region) based on in situ-produced 10Be exposure dating. (1st September 2017) - ; Aumaître, Georges; Bourlès, Didier L.; Keddadouche, Karim; Rodríguez-Rodríguez, Laura; Jiménez-Sánchez, Montserrat; Domínguez-Cuesta, María José; Rinterknecht, Vincent; Pallàs, Raimon
Abstract: The Last Glacial Termination led to major changes in ice sheet coverage that disrupted global patterns of atmosphere and ocean circulation. Paleoclimate records from Iberia suggest that westerly episodes played a key role in driving heterogeneous climate in the North Atlantic Region. We used 10 Be Cosmic Ray Exposure (CRE) dating to explore the glacier response of small mountain glaciers (ca. 5 km 2 ) that developed on the northern slope of the Cantabrian Mountains (Iberian Peninsula), an area directly under the influence of the Atlantic westerly winds. We analyzed twenty boulders from three moraines and one rock glacier arranged as a recessional sequence preserved between 1150 and 1540 m above sea level (a.s.l.) in the Monasterio valley (Redes Natural Park). Results complement previous chronologic data based on radiocarbon and optically stimulated luminescence from the Monasterio valley, which suggest a local Glacial Maximum (local GM) prior to 33 ka BP and a long-standing glacier advance at 24 ka coeval to the global Last Glacial Maximum (LGM). Resultant 10 Be CRE ages suggest a progressive retreat and thinning of the Monasterio glacier over the time interval 18.1–16.7 ka. This response is coeval with the Heinrich Stadial 1, an extremely cold and dry climate episode initiated by a weakening of the Atlantic Meridional Overturning Circulation (AMOC). Glacier recession continued through the Bølling/Allerød period as indicate the minimum exposure ages obtained from a cirque moraine and a rock glacier nested within this moraine, which yielded ages of 14.0 and 13.0 ka, respectively. Together, they suggest that the Monasterio glacier experienced a gradual transition from glacier to rock glacier activity as the AMOC started to strengthen again. Glacial evidence ascribable to the Younger Dryas cooling was not dated in the Monasterio valley, but might have occurred at higher elevations than evidence dated in this work. The evolution of former glaciers documented in the Monasterio valley seems consistent with previous 10 Be chronologies reported in other mountain ranges of the Iberian Peninsula, which have been recalculated according to a common production rate and scaling scheme. However, the re-evaluation of published 10 Be chronologies has highlighted the fact that glacial evidence previously ascribed to the Younger Dryas might be more limited than previously thought and the need for additional studies to characterized the extent of glaciers during the Younger Dryas cooling. Highlights: Last deglaciation in the Cantabrian Mts. is reconstructed and dated using 10 Be CRE. Moraines formed between 18.1 and 14 ka; rockglaciers remained active until 13 ka. Previous deglacial 10 Be chronologies from other Iberian massifs are recalculated. Evidence ascribable to the YD in Iberia may be more limited than previously thought.